Assessment of the Current State of Stimulation of Human Capital Development in Industry in the Republic of Azerbaijan - Latif Zeynalli (International Society of Philosophy and Cosmology (ISPC), 2021)
The greater the added value created by human labor, the greater the return on capital, so the return on capital must be increased. Investing in human capital is regarded as the most efficient and costeffective societal investment in developed countries. Human capital is one of the most important factors in boosting economic potential and overall growth. The increasing importance of human capital in ensuring economic development necessitates its study in the industry. As society progresses and changes occur, the scope of the quality elements that shape human capital broadens to include characteristics such as citizenship, political and legal culture, upbringing, morality and education, health, and cultural level. These indicators indicate that industrial enterprises with these indicators can operate for a longer period of time and more sustainably than others. As a result, the mechanisms for stimulating human capital in the Azerbaijani industry were assessed in this research paper, which used statistical data from the State Statistics Committee of the Republic of Azerbaijan. The leading indicators that can help the sector’s human capital development have been identified.